2018
DOI: 10.1590/0100-5405/178172
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of grain discoloration in the main rice genotypes of Corrientes Province, Argentina

Abstract: Rice grain discoloration affects grain yield and quality. Corrientes is the main rice producing province in Argentina. Previous studies were carried out in this province, where only panicle incidence (PI) was evaluated. In view of the need to obtain more agronomic parameters to more exhaustively investigate the effects caused by this disease, the present study was carried out to evaluate panicle incidence (PI), percentage of discolored grains per panicle (GD), weight loss (WL), disease severity index (DSI) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Especies de los géneros Alternaria, Curvularia, Fusarium y Pyricularia han sido identificados como patógenos potenciales en el cultivo de arroz (da Silva-Lobo et al, 2011). La pigmentación de grano contaminado es de color gris, marrón y negro (Figura 1), reduciendo el rendimiento alrededor de 19% y calidad de semilla (Baite et al, 2020;Rivero et al, 2012;Dirchwolf et al, 2018). En México, se ha reportado la resistencia y susceptibilidad de estos patógenos.…”
Section: Manchado De Grano De Arroz Causados Por Hongos Fitopatógenosunclassified
“…Especies de los géneros Alternaria, Curvularia, Fusarium y Pyricularia han sido identificados como patógenos potenciales en el cultivo de arroz (da Silva-Lobo et al, 2011). La pigmentación de grano contaminado es de color gris, marrón y negro (Figura 1), reduciendo el rendimiento alrededor de 19% y calidad de semilla (Baite et al, 2020;Rivero et al, 2012;Dirchwolf et al, 2018). En México, se ha reportado la resistencia y susceptibilidad de estos patógenos.…”
Section: Manchado De Grano De Arroz Causados Por Hongos Fitopatógenosunclassified
“…(Gutiérrez et al, 2002). Results of previous studies have shown that, in Corrientes province, RGD presents 100% prevalence and up to 40% incidence (Dirchwolf et al, 2018).…”
Section: Introductionmentioning
confidence: 96%